Contraceptive Methods Used by the Selective Rural Tea Garden Workers of Sylhet (Medicine Today, 2022)
Introduction: This study was focused on contraceptive methods used by the selective Tea garden workers of Sylhet. The aim was to explore the used of the contraceptive methods and factors influencing the use of the contraceptive methods along with socio-demographic profile of the tea garden workers.Materials and Methods: It was descriptive type of cross-sectional study carried out in some selective tea garden of Sylhet from July-December, 2020. 150 respondents were selected by purposive type of non-probability sampling method. Data were collected by a pretested mixed type questionnaire.Results: The study revealed that 90 (60%) of workers belonged to of 20-29 years age group. The mean age was 33.87 ± 8.97. Most of the respondents 104 (69.3%) were female, 117 (78%) were followers of Hinduism, 109 (72.7%) were illiterate, 136 (90.7%) were from the nuclear family and 129 (86%) were belonged to lower class. Majority of the workers 136 (90.7%) were using contraceptive methods, among them 78 (57%) were using injectable contraceptive but no one use permanent methods. Most of them used contraceptive methods for prevent unwanted pregnancy and reduced family expenditure that was 46 and 40 (34% and 29%). The survey assessed the positive association between use of contraceptive methods and sex, religion (p